Genome-wide development and utilization of Simple Sequence Repeats in Chinese cabbage (Brassica rapa L. ssp. pekinensis) - Ying Gao; Na Li; Xiaoguang Li; Yin Lu; Daling Feng; Xiaomeng Zhang; Aixia Gu; Yunjia Ge; Javaria Tabusam; Mengyang Liu; Yanhua Wang; Xueping Chen; et al. (Vegetable Research)
With the complementation of whole-genome sequencing of Chinese cabbage, it is necessary to develop genome-wide Simple Sequence Repeat (SSR) markers and analyse their characteristics, which will bring a revolution in the molecular marker-assisted breeding of Chinese cabbage. In this study distribution and characteristics of SSR loci in the genome of Chinese cabbage 'Chiifu' was analyzed. Finally, a total of 173,892 SSR markers that occurred in 10 chromosomes were identified, and Perfect Repeat Motifs (P type) which is a main form of SSR loci with a mean distance of 1.89 kb/SSR was identified. Among them, mono-, di-, and tri-nucleotide repeat motifs were equally distributed across chromosomes compared with tetra-, penta-, and hexa-nucleotide repeat motifs. The largest proportion of SSR loci consisted of mono- and dinucleotide repeat motifs, which accounted for 93.04% of the total SSR loci. A/T and AT/TA were the most abundant motifs, accounting for 97.61% and 64.05% of the mono- and dinucleotide repeats, respectively. Furthermore, 200 SSR markers were used for the amplification of 12 Chinese cabbage germplasm, in which 30 were highly polymorphic. These SSR markers were further used for the association analyses of flowering time of 190 Chinese cabbage accessions. The results revealed that 9 and 10 alleles were associated with bolting and flowering time, respectivley. The results show that development of SSR markers is feasible and useful in marker assisted selection of Chinese cabbage.